Mobile pervasive augmented reality systems the role of user preferences in perceived quality of experience - Pascoal, R. (2019)
This work addresses reasons and aspects required to boost the acceptance and use of mobile pervasive augmented reality systems - MPARS - for outdoor applications and the need to develop context-aware close to- real-time feedback mechanisms that take into consideration a continuous measurement of Quality of Experience. For this purpose, we delve into how user preferences can be integrated in context-aware feedback systems, proposing a Quality of Experience theoretical model derived from an analysis on technology adoption models and user preferences. The how and why such model can be integrated into future solutions is also addressed.